2020
DOI: 10.1111/ajt.16237
|View full text |Cite
|
Sign up to set email alerts
|

Striving for Equity in Transplant

Abstract: This month’s installment of “The AJT Report” delves into how the global push for racial equity has underscored the need to address current racial disparities in the transplantation community. In addition, we report on the current shortage of a frequently used immunosuppressant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…Health disparities in kidney transplants have remained prevalent in the United States despite ongoing efforts to overcome systemic racism. 3,4 A recent study analyzing the readability of the top 10 websites from an online search for deceased and live kidney donation found that the content was written at a college level. 5 Patient and family members' understanding of transplant health…”
Section: Discussionmentioning
confidence: 99%
“…Health disparities in kidney transplants have remained prevalent in the United States despite ongoing efforts to overcome systemic racism. 3,4 A recent study analyzing the readability of the top 10 websites from an online search for deceased and live kidney donation found that the content was written at a college level. 5 Patient and family members' understanding of transplant health…”
Section: Discussionmentioning
confidence: 99%
“…2 Examples of inequities exist at every stage of the transplant process, and dedicated resources are needed to eliminate the influence of systemic racism. 3 African Americans are 37% less likely than White patients to be referred for transplant evaluation prior to initiation of dialysis. 2 Non-English speaking patients are less likely to complete the evaluation process and become active on the waitlist.…”
Section: Inequity In Kidney Transplantationmentioning
confidence: 99%
“…Last year, the American Society of Transplantation announced the members of its Inclusion, Diversity, Equity, and Access to Life (IDEAL) Task Force, people whose voices have informed the American Journal of Transplantation (AJT) . They include IDEAL chair Marie Chisholm‐Burns, PharmD, MPH, MBA, of the University of Tennessee College of Pharmacy in Memphis, and Elisa Gordon, PhD, MPH, of Northwestern University in Chicago 1–3 . AJT and “The AJT Report” are committed to continue serving as a vehicle for these critical conversations.…”
Section: Uniting Against Structural Racismmentioning
confidence: 99%
“…They include IDEAL chair Marie Chisholm-Burns, PharmD, MPH, MBA, of the University of Tennessee College of Pharmacy in Memphis, and Elisa Gordon, PhD, MPH, of Northwestern University in Chicago. [1][2][3] AJT and "The AJT Report" are committ ed to conti nue serving as a vehicle for these criti cal conversati ons.…”
mentioning
confidence: 99%